Significance of Fetal Trans-Cerebellar Diameter And Fetal Kidney Length In Fetal Biometry - Abdel Wahed, Hamada Ashry; Yassin Ali, Mahmoud Sedki; M Osman , Sara; Al Abdein Farid, Eman Zein; Mohammed Nazif , Ahmed Abu Al Laill; eldien elkady , Maged Salah; Mohammed Abdelaziz, Khaled; awad khafagy , Haythem awad; Abou Sharaf , Ahmed Mostafa Saad; M Khalil, Eman (Journal of Neonatal Surgery, 2025)
Background: Antepartum care and treatment planning rely on precise gestational age (GA) assessment. Tansversecerebellar diameter (TCD) and fetal kidney length (FKL) are effective for estimating GA in cases with ambiguous dates or suspected intrauterine growth restriction (IUGR). Objective: To evaluate the diagnostic precision of TCD and FKL measures in determining GA throughout the 2nd and 3rd trimesters, in comparison to other established parameters. Method: The study included 170 pregnant women at the 2nd and 3rd trimesters. The TCD, FKL, biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and femur length (FL) were evaluated to ascertain GA in two cohorts: the first (14-28 weeks) and the 2nd (29-40 weeks) using sonographic evaluation. Results: This study discovered that GA enhances FKL and TCD, exhibiting a high correlation coefficient, which signifies robust agreement and consistency, with no discrepancies in the 3rd trimester. This study identified a significant correlation between FKL and TCD and fetal GA, demonstrating a steady rise throughout pregnancy. Conclusion: TCD and FKL may separately predict GA throughout the 2nd and 3rd trimesters.